Protein Kinase C: One Pathway towards the Eradication of Latent HIV-1 Reservoirs - Lisa N. McKernan; David Momjian; Joseph Kulkosky (Advances in Virology)
An effective means to eradicate latent reservoirs in HIV-1-infected individuals remains elusive. Attempts to purge these reservoirs were undertaken over a decade ago without success. The subsequent lapse in further clinical attempts since may have been justified as our knowledge of the mechanisms which underpin the latent state still evolves. Although additional novel molecular antagonists of HIV-1 latency have subsequently been reported, these candidate agents have not been tested in human trials for reservoir ablation. This review provides an overview of the protein kinase C (PKC) pathway which can be modulated by small molecular agents to induce the expression of latent HIV-1 from within infected reservoir cells. Some of these agents have been tested against select cancers with seemingly tolerable side effects. As such, modulation of the PKC pathway may yet be a viable mechanism toward HIV-1 reservoir eradication.